KAJIAN HERMENIUTIKA PADA KARYA MAHAYASA DENGAN ARTIFICIAL INTELLIGENCE - Wijaya, I Putu Sinar; Budayana, I Wayan Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study examines the meaning of Mahayasa's digital artworks produced with the aid of Artificial Intelligence technology through a hermeneutic approach. Mahayasa's works, which combine traditional Nusantara cultural values ​​with modern AI-based aesthetics, present complex and multi-layered interpretative dimensions. Through the hermeneutic framework of Gadamer and Ricoeur, this study highlights how the process of